Evapotranspiration, crop coefficient and water use efficiency of onion cultivated under different irrigation depths - Wendy K. Matsunaga; Vicente de P. R. da Silva; Victória P. Amorim; Eliton S. G. Sales; Sílvia M. Dantas; André B. Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to determine crop evapotranspiration through the soil water balance, the crop coefficient and water use efficiency of the onion (Allium cepa L.) in a system with four irrigation regimes, cultivated in the semiarid region of northeastern Brazil. Two field experiments were carried out during the rainy and dry periods of the region in 2018, using the treatments of 100% (T1), 75% (T2), 50% (T3) and 25% (T4) of the reference evapotranspiration for daily water replacement and five replicates for each treatment. It was verified that crop evapotranspiration varies according to the water availability in the soil; however, the highest water use efficiency occurred for the T3 treatment. The T1 treatment obtained the highest estimated yield, 43.86 tons ha-1, while T4 obtained 13.47 tons ha-1, the lowest estimated yield among the treatments, and this difference was statistically significant (p ≤ 0.05) by F test. The crop coefficients obtained were 0.68, 0.89, 0.99 and 0.73 for the initial, vegetative, bulbing and maturation stages, respectively.